1987
DOI: 10.1016/0021-9797(87)90305-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of self-preserving spectra in smoluchowski's coagulation theory

Abstract: The cluster size distribution Ck(t) in aggregation and coagulation phenomena for large cluster sizes k and large times t approaches a scaling form of self-preserving spectrum ck(t)'~ s -2 ~o(k/s), where s(t) is the mean cluster size. In a mean field approach the scaling form ~o(x) is described by a nonlinear integrodifferential equation, obtained from Smoluchowski's coagulation equation. To verify some theoretical predictions and to provide quantitative information on the scaling form we develop a fixed point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The continuous distribution of particle sizes is a non-linear integro-differential equation whose kernel depends on the size of the colliding aggregates. Meesters and Ernst [151] demonstrated that the use of a constant kernel in this equation leads to an exponential frequency distribution of particle sizes. Smoluchowski result approaches this exponential distribution at long times.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous distribution of particle sizes is a non-linear integro-differential equation whose kernel depends on the size of the colliding aggregates. Meesters and Ernst [151] demonstrated that the use of a constant kernel in this equation leads to an exponential frequency distribution of particle sizes. Smoluchowski result approaches this exponential distribution at long times.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the particle mean volume s(t) and the profile g S are to be determined and depend on the coagulation kernel a but not on the "details" of the initial data. Several computational studies have been performed to check the dynamical scaling hypothesis (1) and seem to support its validity [10,12,14,20]. Also, rather precise information on the profile g S have been obtained by formal arguments in [6,19].…”
Section: Introductionmentioning
confidence: 94%
“…The formulae (18) and (19) also formally follow from (20) with ψ(y) = y and ψ(y) = y 2 , respectively. Since these functions do not belong to W 1,∞ , an approximation argument has to be used, first with ψ(y) = min {y, R} and then with ψ(y) = y min {y, R}.…”
Section: Liapunov Functionalsmentioning
confidence: 99%
“…In the latter one attempts to obtain the breakage functions from experimental PSD data. The present work (which may be considered the breakage analogue of coagulation study in [7]) is focused on the development of a general numerical method for problems involving a self-similar PSD and on the study of its shape for several forms of breakage kernel for which no analytical solutions exist.…”
Section: Introductionmentioning
confidence: 99%